Foundations of Heterogeneous Integration: An Industry-Based, 2.5D/3D Pathfinding and Co-Design Approach - Yazdani, Farhang (Springer International Publishing, 2018)
This book provides a practical, hands-on approach to teach the foundation of 2.5D/3D heterogeneous design. Based on the author's extensive, industrial experience, this book enables integrated circuit design techniques that provide more memory to the logic chip, also allowing for mixing chips and intellectual property blocks from any vendor to build a more complex chip, more efficiently and cost effectively. Various practical examples and industrial projects are presented throughout the book, including questions and term projects at the end of each chapter. This book is a great resource for practicing engineers and can be used at universities to teach a course at the senior undergraduate and graduate level. Provides knowledge and skills necessary to design wirebond, flip chip and system in package (SIP) products; Provides practical solutions for 2.5D/3D memory and logic integration, explaining a complex, multidisciplinary topic in straightforward terms; Demonstrates a unique co-design methodology for optimizing cross domain heterogeneous integration, including examples, pathfinding, packaging strategy, interposer structure, etc.; Includes real, industry-based examples to give readers hands-on practical design experience.